Reconstructing the polder: negotiating property rights and 'blue' functions for land. (9th February 2009) - Roth, Dik; Winnubst, Madelinde
Dikes were the core of Dutch river flood protection. Near-floods in 1993 and 1995 and debates about climate change, however, led to a rethinking of existing approaches. In the policy directive 'Room for the River' the focus has shifted from infrastructure (dikes) to spatial measures (bypasses, dike relocations, 'green' rivers). While people and land used to be separated from water by dikes, this new policy intensifies water-society interactions. This has important social, spatial and property consequences for inhabitants, and requires a style of governance based on negotiations between the government and societal actors. In this article, we discuss the case of the Overdiep polder along the river Meuse where a 'Room for the River' project is being implemented. The inhabitants have developed a plan for a spatial redesign of the polder to make peak water retention possible. We discuss key aspects of the complex negotiations about property, security and continuity of living and farming in the polder.